Study the Effect of Different Application Level of Tobacco Compost Waste on some Physical Soil Charactarestics (Latakia University Journal -Biological Sciences Series, 2022)
A field experiment was conducted in Sanaaubar Research Station (Jableh Provence) in spring of 2020-2021.Different levels of tobacco waste compost (C0=0, C1=10, C2=20, AND C3=40 ton/h-1) was added to a sandy loamy soil in wich growing maize crop.The experiment followed a completely randomized designed with three replicates for each treatment. At the end of the growing season (after 75-85 days), soil samples withdrawal from the 0-30 cm depth from each plot for measurements of (OM, mean weight diameter (MWD), bulk density, porosity).The results show a gradual significant increase in soil organic matter contents by a rate of (15,30, and 54%) with increasing application level of tobacco compost compared to the control treatment (C0). This led to a significant decrease in bulk density compared to C0 treatment by about (0.06, 0.27, and 0.47 g/cm3) in the C1, C2, and C3 treatment, respectively.Total porosity increased in all treatments receiving tobacco compost. Micropores also significantly increased on the expense of macropores in all C1, C2, and C3 treatments compared to the control C0 treatment. The stability of the soil texture was improved in compost treatments in which value of MWD reached in C3treatment 1.67 mm, an increase of 71.85% compared to the control. The improved physical properties was reflected in growth and productivity of maize crop in which yield reached 18 ton/h-1 in C3 treatment receiving 40 ton/h-1 of tobacco compost.